Criminal Policy in Resolving Cases of Theft by Children - Akbar, Rizki (International Journal of Business, Law, and Education, 2024)
Children are an inseparable part of the survival of human life and the sustainability of a nation and state. In substance, the form of legal protection for children in conflict with the law must be prioritized by law enforcement officials. One form of protection contained in positive law is contained in the provisions of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, using a diversionary settlement. In this study, there are several problems, among others, in the form of settlement of the crime of theft committed by children according to positive law. As well as obstacles in the process of resolving the diversion of the crime of theft committed by children according to positive law. This research is a type of normative juridical research. Meanwhile, the approach used in this research is the Legislative Approach and the Conceptual Approach